SCIENCE LABORATORIES IN HIGHER SECONDARY SCHOOLS OF MIZORAM (International Journal of Food and Nutritional Sciences, 2022)
Science is the basis of most modern technological development. Food and nutritional sciences which are applied sciences depend heavily on a good and solid grounding in science. But Science education, without practical experience is abstract and its deep impact is difficult to understand. Especially at the higher secondary level when students have already made their choice to study science, they deserve to get the best exposure to scientific phenomena. The present research was a University project funded by, Mizoram Science and Technology Innovation Council, an autonomous body of the Government of Mizoram. An exhaustive attempt was made to find out the status of science laboratories in three subjects like physics, chemistry and biology in higher secondary schools of Mizoram. It was found that only 22% of schools had more than 75% of specified apparatus and equipment in physics laboratory and 61% schools had more than 75% of equipment and apparatus in chemistry laboratory. It was also found out that under biology laboratories small 28% only schools had more than 75% apparatus and equipment. Therefore, the study revealed in clarity the robust practical approach science was given in some schools and just how weak science education was in many schools within the state of Mizoram at the time the study was undertaken.